Influence of Age group on Job Satisfaction in Academia - Milan Shrestha (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose - Job Satisfaction (JS) has seen an upsurge concern in the arena of school management and it is highly associated with the age groups of school teachers. Thus, this study focused to ascertain the level of JS and examine it via age groups of school teachers. Design - The scholar applied a cross-sectional survey design in post-positivist paradigm. The data were amassed from 345 school teachers of a cluster via self-administer questionnaire and analyzed with descriptive statistics and ANOVA test. In the meantime, social exchange theory was employed to scrutinize the results. Findings - This study found that the school teachers expressed moderate satisfaction in the job. Likewise, the age groups significantly influence the JS among school teachers. More specifically, the senior age group teachers expressed more satisfaction in the job than other groups of the teacher. Subsequently, these job satisfied teachers contribute to more job commitment, effectiveness and work performances in the school. Furthermore, JS facilitates school to achieve elevated academic success. Implications - The study endows with the concrete approach for other forthcoming scholar to explore the contribution of age groups on JS among academia.